Adverse event reporting in Czech long-term care facilities - Hěib, Zdenřk; Vychytil, Pavel; Marx, David (International journal for quality in health care, 2013)
OBJECTIVE: To describe adverse event reporting processes in long-term care facilities in the Czech Republic. DESIGN: Prospective cohort study involving a written questionnaire followed by in-person structured interviews with selected respondents. SETTING: Long-term care facilities located in the Czech Republic. PARTICIPANTS: Staff of 111 long-term care facilities (87% of long-term care facilities in the Czech Republic). INTERVENTION(S): None. RESULTS: Sixty-three percent of long-term health-care facilities in the Czech Republic have adverse event-reporting processes already established, but these were frequently very immature programs sometimes consisting only of paper recording of incidents. Compared to questionnaire responses, in-person interview responses only partially tended to confirm the results of the written survey. Twenty-one facilities (33%) had at most 1 unconfirmed response, 31 facilities (49%) had 2 or 3 unconfirmed responses and the remaining 11 facilities (17%) had 4 or more unconfirmed responses. CONCLUSIONS: In-person interviews suggest that use of a written questionnaire to assess the adverse event-reporting process may have limited validity. Staff of the facilities we studied expressed an understanding of the importance of adverse event reporting and prevention, but interviews also suggested a lack of knowledge necessary for establishing a good institutional reporting system in long-term care.
Keywords: ubytovací zařízení; Qualitative Research; průzkumy a dotazníky; Medical Errors; postoj zdravotnického personálu; Surveys and Questionnaires; lidé; Program Evaluation; bezpečnost pacientů; Long-Term Care; Mandatory Reporting; Attitude of Health Personnel; hodnocení programu; prospektivní studie; Prospective Studies; Czech Republic; dlouhodobá péče; Česká republika; Residential Facilities; oznamovací povinnost; chybná zdravotní péče; Patient Safety; kvalitativní výzkum; Humans